Osteopontin Gene Polymorphisms rs1126616 C>T and rs1126772 A>G are Associated with Atopic Dermatitis in Polish Population - Kaleta B; Lachota M; Łukaszkiewicz J; Woźniacka A; Bogaczewicz J (The Application of Clinical Genetics, 2021)
Beata Kaleta,1 Mieszko Lachota,1,2 Jacek Łukaszkiewicz,3 Anna Woźniacka,4 Jarosław Bogaczewicz5 1Department of Clinical Immunology, Medical University of Warsaw, Warsaw, Poland; 2Doctoral School, Medical University of Warsaw, Warsaw, Poland; 3Department of Biochemistry and Clinical Chemistry, Medical University of Warsaw, Warsaw, Poland; 4Department of Dermatology and Venereology, Medical University of Lodz, Lodz, Poland; 5University of Economics and Human Sciences in Warsaw, Warsaw, PolandCorrespondence: Beata KaletaDepartment of Clinical Immunology, Medical University of Warsaw, Nowogrodzka 59 Street, Warsaw, 02-006, PolandTel +48 600 301 690Fax +48 502 21 59Email beata.kaleta@wum.edu.plPurpose: Atopic dermatitis (AD) is a chronic, relapsing inflammatory disease, caused by environmental and genetic factors, which lead to immunological abnormalities. Osteopontin (OPN), also named secreted phosphoprotein 1 (SPP1), is a protein involved in the pathogenesis of numerous autoimmune and inflammatory conditions. However, its role in AD has not been fully elucidated. Therefore, we aim to gain an insight into the role of OPN in AD pathogenesis through investigating its gene single nucleotide polymorphisms (SNPs) and their possible associations with disease clinical features.Patients and Methods: A total of 182 Caucasian participants (45 AD patients and 137 gender- and age-matched controls) were studied. Genomic DNA was isolated from peripheral blood samples. Genotyping for the rs1126616 C>T, rs1126772 A>G, rs9138 A>C, and rs3841116 T>G SNPs was performed by real time polymerase chain reaction (RT-PCR).Results: The frequency of the minor TT genotype and the T allele of rs1126616 C>T was higher in AD patients compared to controls (P = 0.019, OD = 4.86, 95% CI = 1.46– 16.20, and P = 0.047, OR = 1.77, 95% CI = 1.04– 3.00, respectively) and was associated with the higher prevalence of asthma (P = 0.017, OR = 3.73, 95% CI = 0.71– 19.67, and P = 0.004, OR = 3.96, 95% CI = 1.53– 10.25, respectively). Likewise, the minor GG genotype and the G allele of rs1126772 A>G were more frequent in AD patients (P = 0.026, OR = 3.27, 95% CI = 1.29– 8.33, and P = 0.013, OR = 1.94, 95% CI = 1.18– 3.21, respectively) and were associated with the increased incidence of asthma (P = 0.016, OR = 5.06, 95% CI = 1.14– 22.49, and P = 0.002, OR = 4.40, 95% CI = 1.71– 11.35, respectively). Furthermore, haplotype frequency estimation determined the four-loci haplotype TGCT, as a significant risk factor for AD compared to controls (P = 0.031, OR = 9.48, 95% CI = 1.23– 71.91).Conclusion: Our results suggest that the variation in the OPN gene might be associated with AD and increased incidence of asthma in Caucasians. Further studies should be conducted to look into the possible role of OPN as a biomarker for AD.Keywords: asthma, atopic dermatitis, gene, osteopontin, polymorphism, AD, OPN